IDENTIFIKASI KEDALAMAN AIR TANAH DAN INTRUSI AIR LAUT DENGAN METODE GEOLISTRIK KONFIGURASI SCHLUMBERGER DI DESA BENTENG KECAMATAN MALANGKE - Fitri Jusmi; Selviani Basri (Applied Physics of Cokroaminoto Palopo, 2020)
Research has been carried out in Benteng Village, Malangke District, NorthLuwu Regency by using the schlumberger configuration geoelectric method to determine the subsurface lithology related to the identification of groundwater depth and sea water intrusion in the area. In this study, each measurement path has a length of 150 meters. The resulting data is in the form of a resistance value and is used to find the apparent resistivity value. The data is then processed using IPI2win software to obtain lithological images of subsurface rocks. From the results of the inversion using IPI2win software, it can be seen that the depth of groundwater and sea water intrusion in the area. This can be seen from the results of the interpretation based on geological conditions and the resistivity value shows that seawater intrusion occurs on line 2, starting at a depth of 0.5-9.4 meters with a resistivity value of 1.7-5.9 Ώm. A good groundwater layer to be used as a borehole is on line 1, starting from a depth of 1. 1-22.01 meters with a resistivity value ranging from 53.2-160.5 Ώm, because on line 1 sea water intrusion is not found.